DO GLOBAL AO LOCAL: AS METAMORFOSES DO TRABALHO NO PERÍODO DE 1980 A 2010 - Santos, Roberto Mesquita (2011)
The changes which have occurred at work have been linked to hegemony of principal economical powers of the world which have originated from 1980 to 2010, accumulation logical, based upon the globalization and Neoliberalism which have reached all over the world by provoking unemployment as well as lack of work, as an example in Bahia. Such a research has as aim to show the consequences of work changes in Bahia in period of globalization intensification. Therefore, it has been developed studies and caught data from Work International Organization (OIT) Unemployment and Employment General Register (CAGED), Social Information Annual Relation (RAIS), Statistics Geography Brazilian Institute (IBGE) and Social Economical Studies Bureau of Bahia (SEI). Such studies have lead to a comprehension of structural reasons of lack of work and unemployment which have appeared in Bahia for 40 years.